Analyzing the International Response to the 2020 July Border Clashes Between Armenia and Azerbaijan - Zohrabyan, Yelena; Muradyan, Lilit (History and Culture, 2024)
The article analyzes the military operations launched by Azerbaijan along the internationally recognized border of Armenia’s Tavush region from July 12-16, 2020. It presents the sequence of events that took place in both countries during the military clashes, and provides an assessment of the immediate responses to the border military operations by global, regional, and local actors, using content analysis methodology. The article also examines the involvement of international organizations in the conflict resolution process, comparing the statements and actions made by these organizations. The role of major powers and influential actors in conflict resolution is also discussed, comparing their diplomatic efforts and positions. The dynamics of military operations, diplomatic measures, and approaches taken by both Armenia and Azerbaijan after the clashes are studied.